Sistem Load Balancing Menggunakan Least Time First Byte dan Multi Agent System - Muhammad Faizal Afriansyah; Maman Somantri; Munawar Agus Riyadi (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
Network activity has increased in every year due to rapid growth of internet users. This phenomenon eventually increases the load server. The high load on server makes server down. The proposed system to handle the issue is using Least Time First-Byte algorithm and multi-agent system in distributed load balancing. The agent collects information resources on the backend servers and communicates with the agents. The Least Time First-Byte algorithm is then combined with the information resources from the agent, called as Least Time First Byte with Multi Agent System (LFB-MAS). The simulation results show that LFB-MAS performs load balance efficiently to all server and provides better performance. The LFB-MAS can process 100% from the 1,800 requests, whereas WLC algorithm is only capable of processing 74.50% from 1,800 requests and LFB without agent is only capable of processing 75.61% from 1,800 requests. The results prove that LFB-MAS can handle high tasks or requests and is reliable.